Interleukin-9 over-expression and T helper 9 polarization in systemic sclerosis patients. (23rd August 2017) - Guggino, G; Lo Pizzo, M; Di Liberto, D; Rizzo, A; Cipriani, P; Ruscitti, P; Candore, G; Gambino, C M; Sireci, G; Dieli, F; Giacomelli, R; Triolo, G; et al.
Summary: T helper 9 (Th9) cells and interleukin (IL)-9 are involved in the pathogenesis of several autoimmune diseases. The exact role of IL-9 and Th9 cells in patients with systemic sclerosis (SSc) have not yet been studied adequately. IL-9, IL-9R, transcription factor PU.1 (PU.1), IL-4, thymic stromal lymphopoietin (TSLP) and transforming growth factor (TGF)-β expression were assessed in skin and kidney biopsies of SSc patients and healthy controls (HC) by immunohistochemistry (IHC). The cellular source of IL-9 was also analysed by confocal microscopy analysis. Peripheral IL-9-producing cells were also studied by flow cytometry. The functional relevance of IL-9 increased expression in SSc was also investigated. Our results demonstrated a strong expression of IL-9, IL-9R, IL-4, TSLP and TGF-β in skin tissues of patients with both limited and diffuse SSc. IL-9 expression was observed mainly in the context of skin infiltrating mononuclear cells and keratinizing squamous epithelium. IL-9 over-expression was also observed in renal biopsies of patients with SSc. IL-9 producing cells in the skin were identified as Th9 cells. Similarly, Th9 cells were expanded and were the major source of IL-9 among SSc peripheral blood mononuclear cells (PBMC), their percentage being correlated directly with the modified Rodnan skin score. Infiltrating mononuclear cells, mast cells and neutrophils expressed IL-9R. In in-vitro studies stimulation with rIL-9 significantly induced NET (neutrophil extracellular traps) release by dying cells (NETosis) in neutrophils, expansion of mast cells and increase of anti-systemic scleroderma 70 (Scl70) production by B cells. Our findings suggest that Th9 cells and IL-9 could be implicated in the pathogenesis of SSc. Graphical Abstract: